Heredity, physiology and mapping of a chlorophyll content gene of rice (Oryza sativa L.) - Wang, Fenghua (Journal of plant physiology, 2008)
A single dominant gene Gc controls the trait of high chlorophyll (Chl) content in rice (cultivar (cv.) Zhenshan 97B). The contents of Chl b and total Chl increased 100% and 25%, respectively, when Gc was introduced. In addition, photosynthetic rate, biomass and grain yield also increased by 20%, 17% and 16%, respectively. Three simple sequence repeats (SSR) markers (rm462, rm6340 and rm6464) that are linked to Gc were identified by amplification of DNA samples from near-isogenic lines using two hundred pairs of primers. The genetic distances on the short arm of rice chromosome 1 between Gc and rm6464, rm6340 and rm462 were 0, 0.588 and 1.18 cM, respectively